2022
DOI: 10.1155/2022/5007930
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics-Containing Mucoadhesive Gel for Targeting the Dysbiosis Associated with Periodontal Diseases

Abstract: Objective. Periodontitis is a common disorder that leads to the loss of both tooth and personal well-being, contributing to worsen the risk for metabolic and cardiovascular diseases. Recently, probiotics, characterized by rapid oral dispersion, have been topically used. Here, we present data of a mucoadhesive gel containing probiotics, capable of ensuring a slow release of bacteria to prevent and treat periodontitis. Methods. An original mucoadhesive gel (AL0005) that is anhydrous and of food grade, loaded wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Results obtained from the competition tests (inhibition zone) were consistent with those obtained in the previous project [ 19 ], confirming the anti-bacterial activity of the tested ingredients of the product, although evaluated by means of in vitro assays. In the second assessment, the antimicrobial action of the single herbal extracts, of the probiotic mixture, and of the different matrices was measured.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Results obtained from the competition tests (inhibition zone) were consistent with those obtained in the previous project [ 19 ], confirming the anti-bacterial activity of the tested ingredients of the product, although evaluated by means of in vitro assays. In the second assessment, the antimicrobial action of the single herbal extracts, of the probiotic mixture, and of the different matrices was measured.…”
Section: Resultssupporting
confidence: 87%
“…The results presented here are the continuation of a previous exploratory study, where it was demonstrated that probiotics were stable over time (more than one year) and were slowly released into the oral cavity after application, if formulated in an anhydrous mucoadhesive gel. We had also demonstrated the effectiveness of this formula in contrasting bone reduction following an inflammatory stress and in counteracting—in vitro—some pathogenic bacteria belonging to the “red complex” [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorhexidine digluconate 0.2% was included as positive inhibition control. Results obtained from the competition tests (inhibition zone) were consistent with those obtained in the previous project [19], confirming the anti-bacterial activity of the tested ingredients of the product, although evaluated by means of in vitro assays. In the second assessment, the antimicrobial action of the single herbal extracts, of the probiotic mixture, and of the different matrices was measured.…”
Section: Antimicrobial Activity: Antagonist Effectssupporting
confidence: 87%
“…Specific strains of probiotic bacteria including L. plantarum GOS42 have potential for use in oral care products to reduce gingival inflammation, they showed downregulation of inflammatory mediators released by ex-vivo human monocytes in response to bacterial LPS, with potent anti-inflammatory effects, which were largely independent of their viability (25) . Amore recent study in 2022 presented data of a locally applied mucoadhesive gel enriched with Lactobacillus probiotic strains to prevent and treat periodontitis (26) .…”
Section: Discussionmentioning
confidence: 99%